Using epigenetic networks for the analysis of movement associated with levodopa therapy for Parkinson's disease. (August 2016) - Turner, Alexander P.; Lones, Michael A.; Trefzer, Martin A.; Smith, Stephen L.; Jamieson, Stuart; Alty, Jane E.; Cosgrove, Jeremy; Tyrrell, Andy M.
Abstract: Levodopa is a drug that is commonly used to treat movement disorders associated with Parkinson's disease. Its dosage requires careful monitoring, since the required amount changes over time, and excess dosage can lead to muscle spasms known as levodopa-induced dyskinesia. In this work, we investigate the potential for using epiNet, a novel artificial gene regulatory network, as a classifier for monitoring accelerometry time series data collected from patients undergoing levodopa therapy. We also consider how dynamical analysis of epiNet classifiers and their transitions between different states can highlight clinically useful information which is not available through more conventional data mining techniques. The results show that epiNet is capable of discriminating between different movement patterns which are indicative of either insufficient or excessive levodopa.